Kerjasama Indonesia-Filipina dalam Menangani Pendanaan Terorisme Berbasis Money Laundering - Nelin Dias Pratiwi; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations Diponegoro, 2022)
Indonesia and the Philippines are two countries in Southeast Asia that have a fairly high terrorist presence. The acts of terrorism that occur cannot be separated from funding as a support for member training and the purchase of weapons (bombs). Funding is usually the result of money laundering, the flow of which must be cut off. Terrorists in Indonesia and the Philippines have close networks, both in terms of financing and purchasing weapons. Therefore, this crime needs to be eradicated through cooperation, considering that this crime is atransnational crime. Preventive efforts carried out by the two countries are cooperation through financial intelligence units, namely the Financial Transaction Reports and Analysis Center (PPATK) with the Anti Money Laundering Council (AMLC) and cooperation through financial institutions, namely Bank Indonesia (BI) with Banko Sentral Ng Philipinas (BSP). The purpose of this study is to describe the Indonesia-Philippines Cooperation in Handling Terrorism finacing based on Money Laundering. This research is a descriptive type of qualitative research and uses a congruent analysis technique. An international regime is defined as a set of principles or norms. This concept explains that the regime is defined as a set of principles, norms, rules and procedures for making either implicit or explicit. Even though the country is in a state of anarchy, cooperation can still be done. The results of this study are the existence of Cooperation between Indonesia and the Philippines through financial institutions as an anti-money laundering regime, terrorism financing crimes can be prevented and minimized, so that it also has an impact on reducing terrorism crimes. The suggestion for further research is that there is further research that discusses the opportunities and challenges in dealing with terrorism cases in the future, especially in terms of funding.